2007
DOI: 10.1152/ajpendo.00490.2007
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1 regulates hypoxia- and insulin-induced expression of apelin in adipocytes

Abstract: Glassford AJ, Yue P, Sheikh AY, Chun HJ, Zarafshar S, Chan DA, Reaven GM, Quertermous T, Tsao PS. HIF-1 regulates hypoxia-and insulin-induced expression of apelin in adipocytes. Am J Physiol Endocrinol Metab 293: E1590-E1596, 2007. First published September 18, 2007 doi:10.1152/ajpendo.00490.2007.-Apelin, a novel peptide with significant cardioactive properties, is upregulated by insulin in adipocytes. However, the mechanism by which insulin promotes apelin production is unknown. Hypoxia-inducible factor-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
82
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 44 publications
10
82
0
2
Order By: Relevance
“…Recently, periodontitis has been suggested to contribute to adipose tissue inflammation by promoting insulin resistance [47]. Both OSAS [48] and periodontitis [47] are associated with insulin-resistance, and insulin-induced apelin expression has been demonstrated in adipocytes [49]. The presence and severity of periodontitis might influence salivary apelin and IL-6 originating from buccal adipocytes may be involved in this response.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, periodontitis has been suggested to contribute to adipose tissue inflammation by promoting insulin resistance [47]. Both OSAS [48] and periodontitis [47] are associated with insulin-resistance, and insulin-induced apelin expression has been demonstrated in adipocytes [49]. The presence and severity of periodontitis might influence salivary apelin and IL-6 originating from buccal adipocytes may be involved in this response.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is well established in OSA (Atkeson & Jelic 2008) and is ameliorated by CPAP therapy (Jelic et al 2008). Hypoxia-induced myocardial/endothelial apelin expression has been demonstrated via hypoxia-inducible factor (HIF) pathways (Glassford et al 2007, Ronkainen et al 2007, and the HIF-1 pathway is activated in patients with OSA (Atkeson & Jelic 2008). The pulmonary apelin-producing endothelium is particularly sensitive to hypoxia (Sheikh et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis, electrophoretic mobility shift assays and ChIP have also been used in vitro to determine whether upstream stimulatory factors 1 and 2 (USF1 and USF2) are involved in the expression of apelin in the breast, while in vitro ChIP analyses have shown that endogenous USF up-regulates the expression of apelin in the lactating rat breast (Wang et al 2006). Putative hypoxia response elements (HREs) are present in the apelin gene promoter and intron sequence of various species in silico (Cox et al 2006), and hypoxia has subsequently been found to up-regulate the expression of apelin in cardiac myocytes (Ronkainen et al 2007), and hypoxia-inducible factor 1a (HIF1a) has been reported to induce the expression of apelin in adipocytes (Glassford et al 2007). Additional studies have determined that hypoxia-inducible apelin up-regulation is mediated by HIF1a at a HRE within the APLN intron (conserved in rat and mouse apelin genes) between C813 and C826 bp (Eyries et al 2008), indicating that apelin may play a role in the homeostatic response to low oxygen levels.…”
Section: Gene Regulationmentioning
confidence: 99%
“…Additional studies have determined that hypoxia-inducible apelin up-regulation is mediated by HIF1a at a HRE within the APLN intron (conserved in rat and mouse apelin genes) between C813 and C826 bp (Eyries et al 2008), indicating that apelin may play a role in the homeostatic response to low oxygen levels. Insulin has also been shown to increase the expression of apelin in human and mouse adipocytes, via PI3K, protein kinase C (PKC), mitogen-activated and ERK kinase (MAPK) 1 (Boucher et al 2005) and HIF1a (Glassford et al 2007), while aldosterone has been shown to decrease the expression of apelin in 3T3-L1 adipocytes via the p38 MAPK pathway (Jiang et al 2013). Furthermore, studies on white adipocytes have found that the peroxisome proliferator-activated receptor g co-activator 1a also up-regulates the expression of apelin, possibly indicating that apelin plays a role in energy metabolism (Mazzucotelli et al 2008), while recently in diabetic rats, ghrelin has been reported to reduce apelin mRNA synthesis and release into the lumen (Coskun et al 2013).…”
Section: Gene Regulationmentioning
confidence: 99%